The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/jocd.13215
|View full text |Cite
|
Sign up to set email alerts
|

Prospective application of exosomes derived from adipose‐derived stem cells in skin wound healing: A review

Abstract: Background: Wound healing has always been an intractable medical problem for both clinicians and researchers and a burden for patients both physically and financially. Poor wound healing at the injury site, especially in an exposed site, is associated with an unappealing esthetic appearance in patients and also results in a bad skin barrier, tissue infection and necrosis, loss of main function in extreme cases and other serious local and systemic consequences. There is a crucial and urgent need for newer, more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(80 citation statements)
references
References 72 publications
(67 reference statements)
2
71
0
Order By: Relevance
“…However, MSCs transplantation may induce immunoreactivity to the host [4]. To avoid host-immunoreactivity, MSC-derived exosomes shows a alternative therapeutic attention for regenerative wound repair [5][6][7]. The current study has been demonstrated that MSC-derived exosomes accelerated the wound healing through increased reepithelialization, angiogenesis, and tissue granulation [6].…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…However, MSCs transplantation may induce immunoreactivity to the host [4]. To avoid host-immunoreactivity, MSC-derived exosomes shows a alternative therapeutic attention for regenerative wound repair [5][6][7]. The current study has been demonstrated that MSC-derived exosomes accelerated the wound healing through increased reepithelialization, angiogenesis, and tissue granulation [6].…”
Section: Introductionmentioning
confidence: 66%
“…Recently, studies have shown that the prospective application of MSCs-derived exosomes promoted cutaneous wound healing [5,7,19]. The possible roles of MSCs-derived exosomes in wound healing through promotion of cell proliferation, migration, differentiation, angiogenesis and matrix reconstruction [6].…”
Section: Discussionmentioning
confidence: 99%
“…However, MSCs transplantation may induce immunoreactivity to the host [4]. To avoid host-immunoreactivity, MSC-derived exosomes shows a alternative therapeutic attention for regenerative wound repair [5][6][7]. The current study has been demonstrated that MSCderived exosomes accelerated the wound healing through increased re-epithelialization, angiogenesis, and tissue granulation [6].…”
Section: Introductionmentioning
confidence: 67%
“…Studies have shown that ASC-exos played a positive role in cutaneous wound healing by means of acting on HDFs and HaCaTs and other main target cells through various signal channels ( Figure 1C; Qiu et al, 2020). Ma et al (2019) exposed HaCaTs to hydrogen peroxide (H 2 O 2 ) for establishing a skin lesion model, discovering that ASC-exos could foster HaCaTs proliferation, migration, and inhibit apoptosis through Wnt/β-catenin signaling pathway.…”
Section: Asc-exos In Wound and Scarmentioning
confidence: 99%